Negative pressure wound therapy versus standard treatment in patients with acute conflict-related extremity wounds: a pragmatic, multisite, randomised controlled trial - Andreas Älgå, PhD; Rawand Haweizy, MD; Khaldoon Bashaireh, MD; Sidney Wong, MD; Kalle Conneryd Lundgren, PhD; Johan von Schreeb, ProfPhD; Jonas Malmstedt, PhD (Elsevier, 2020)
Summary: Background: In armed conflict, injuries among civilians are usually complex and commonly affect the extremities. Negative pressure wound therapy (NPWT) is an alternative to standard treatment of acute conflict-related extremity wounds. We aimed to compare the safety and effectiveness of NPWT with that of standard treatment. Methods: In this pragmatic, randomised, controlled superiority trial done at two civilian hospitals in Jordan and Iraq, we recruited patients aged 18 years or older, presenting with a conflict-related extremity wound within 72 h after injury. Participants were assigned (1:1) to receive either NPWT or standard treatment. We used a predefined, computer-generated randomisation list with three block sizes. Participants and their treating physicians were not masked to treatment allocation. The primary endpoint was wound closure by day 5. The coprimary endpoint was net clinical benefit, defined as a composite of wound closure by day 5 and freedom from any bleeding, wound infection, sepsis, or amputation of the index limb. Analysis was by intention to treat. The trial is registered with ClinicalTrials.gov, number NCT02444598, and is closed to accrual. Findings: Between June 9, 2015, and Oct 24, 2018, 174 patients were randomly assigned to either the NPWT group (n=88) or the standard treatment group (n=86). Five patients in the NPWT group and four in the standard treatment group were excluded from the intention-to-treat analysis. By day 5, 41 (49%) of 83 participants in the NPWT group and 49 (60%) of 82 participants in the standard treatment group had closed wounds, with an absolute difference of 10 percentage points (95% CI −5 to 25, p=0·212; risk ratio [RR] 0·83, 95% CI 0·62 to 1·09). Net clinical benefit was seen in 33 (41%) of 81 participants in the NPWT group and 34 (44%) of 78 participants in the standard treatment group, with an absolute difference of 3 percentage points (95% CI −12 to 18, p=0·750; RR 0·93, 95% CI 0·65 to 1·35). There was one in-hospital death in the standard treatment group and none in the NPWT group. The proportion of participants with sepsis, bleeding leading to blood transfusion, and limb amputation did not differ between groups. Interpretation: NPWT did not yield superior clinical outcomes compared with standard treatment for acute conflict-related extremity wounds. The results of this study not only question the use of NPWT, but also question the tendency for new and costly treatments to be introduced into resource-limited conflict settings without supporting evidence for their effectiveness. This study shows that high-quality, randomised trials in challenging settings are possible, and our findings support the call for further research that will generate context-specific evidence. Funding: The Stockholm County Council, the Swedish National Board of Health and Welfare, and Médecins Sans Frontières.